Analysis of displacement evolution characteristics of reverse-dip layered rock slope based on geological geometric partition - Hu, Nanxiang; Zhang, Jiabing; Teng, Lin; Lu, Yiping; Li, Yingchun; Li, Xiaoshuang; Zhu, Chun (Frontiers in Earth Science, 2023)
To investigate the toppling displacement evolution characteristics of anti-dip rock slopes, the Xiaodongcao-Zhengjiadagou bank slope is taken as an engineering case, and firstly, the geological geometric distribution characteristics of the slope are obtained by superimposing the lithology, slope, and elevation raster layers of the slope through ArcGIS, and the geological partition with the largest area is the Lower Triassic Daye Formation, bottom elevation, and medium slope; based on the actual surface displacement monitoring data, the spatio-temporal evolution nephogram of toppling displacement of bank slope every half year is interpolated by Inverse Distance Weight method, and then the last displacement nephogram is assigned to the thousandth and superimposed with the geological geometric partition to obtain the displacement superposition characteristics. The results show that: the obvious zone of horizontal displacement deformation mainly occurs in the front and middle of the bank slope, mainly shear deformation, vertical displacement is primarily in the front and the back edge of the bank slope and the total displacement deformation is more similar to the horizontal displacement; the horizontal displacement value is larger than the vertical displacement value, the horizontal displacement deformation controls the overall deformation of the bank slope; through the analysis of the geometric superposition evolution of the anti-dip rock slope, the displacement superposition strong deformation zone is located at the boundary between the Triassic Jialingjiang Formation (T1j) and the Triassic Daye Formation (T1d).